1995
DOI: 10.3109/01480549509017859
|View full text |Cite
|
Sign up to set email alerts
|

Subchronic Feeding study of Four White Mineral Oils in Dogs and Rats

Abstract: Subchronic 90-day feeding studies were conducted on four highly refined white mineral oils to determine any potential for toxicity in Long-Evans rats (20 per sex per dose level) and beagle dogs (4 per sex per dose level). Each oil was fed at dietary dose levels of 300 ppm and 1500 ppm (w/w). No treatment-related effects of toxicological importance were detected in daily observations of general health or in periodic assessments of food consumption and body weight, hematology, serum clinical chemistry, and urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 7 publications
0
22
0
Order By: Relevance
“…A statistically significant increase of female rats with vacuolation of the lamina propria was seen in the high-dose N l0A group. In the liver, saturated hydrocarbon content ranged from 7.6 to 16.9 mg/g liver in females (Table IV) (34). The absence of histopathologic and other treatment-related effects also is consistent with historical chronic studies on white oils and waxes in Sprague-Dawley rats (100,000 ppm wax for 2 yr) (33), in FDRL rats (50,000 ppm petrolatum for 2 yr) (28), and in BD I, BD III, W strain rats (20,000 ppm white oil for up to 500 days) (32).…”
Section: Hydrocarbon Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…A statistically significant increase of female rats with vacuolation of the lamina propria was seen in the high-dose N l0A group. In the liver, saturated hydrocarbon content ranged from 7.6 to 16.9 mg/g liver in females (Table IV) (34). The absence of histopathologic and other treatment-related effects also is consistent with historical chronic studies on white oils and waxes in Sprague-Dawley rats (100,000 ppm wax for 2 yr) (33), in FDRL rats (50,000 ppm petrolatum for 2 yr) (28), and in BD I, BD III, W strain rats (20,000 ppm white oil for up to 500 days) (32).…”
Section: Hydrocarbon Analysesmentioning
confidence: 99%
“…All prior published and unpublished studies had been without effect. No effects were observed in 90-day feeding studies in LongEvans rats and beagle dogs at doses up to 1,500 ppm of food-grade paraffinic white oils (3 hydrogenated oils at viscosities of 13.8, 31.6, and 65.9 cSt at 40°C and 1 acidtreated oil of 12.3 cSt at 40°C) (12,34). Likewise, subchronic 90-day gavage studies in Sprague-Dawley rats with an acid-treated naphthenic food-grade white oil (35.7 cSt viscosity at 40°C), used as a vehicle control, showed no effects (21).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous subchronic and chronic toxicity studies on MHCs conducted in mice, beagle dogs, and Sprague-Dawley (S-D) and LongEvans rats have demonstrated that these products are safe, because few indications of toxicity have developed (Shubik et al, 1962;McKee et al, 1987;Firriolo et al, 1995;Smith et al, 1995;Miller et al, 1996). Similarly, human exposure to MHCs has not been associated with any significant adverse effects, although human exposure to MHC can result in oil deposits (lipogranulomas) in the liver and other lymphatic tissues (Cruickshank, 1984;Wanless and Geddie, 1985).…”
mentioning
confidence: 99%
“…In addition, subchronic studies in Long Evans rats and Beagle dogs on a related white mineral oil are available (Smith et al, 1995). The studies showed that microcrystalline waxes and high viscosity mineral oils were found to be without statistically significant biological effects at doses up to 1620 mg/kg bw/day for the male rats and up to 1820 mg/kg bw/day for the female rats.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, subchronic studies in Long Evans rats and Beagle dogs on four related white mineral oils are available (Smith et al, 1995). In this study two white mineral oils have a kinematic viscosity of respectively 3.1 and 3.5 mm²/s at 100 °C and carbon numbers respectively between C 14 -C 38 and between C 16 -C 34 .…”
Section: Short-term and Subchronic Toxicitymentioning
confidence: 99%